Implementasi Penerapan Aplikasi Access By KAI Terhadap Kepuasan Pelanggan Di Stasiun Kereta Api Simpang Haru - Fazwa Maura Zacky; Syahrani Indah Putri; Raiend Arasyi Pansla; Sri Rahayu Putri Gusva; Rahmadhona Fitri Helmi (CV. ITTC INDONESIA, 2024)
KAI access is an official application from KAI to make reservations, as a boarding pass tool, train tickets. This application is made to make it easier, especially for KAI passengers, to order tickets, as a medium to find route information and train schedules according to the needs of train passengers. This study discusses the strategy and implementation of customer relationship management of PT. Kereta Api Indonesia (Persero) through the KAI Access application in increasing customer satisfaction at Simpang Haru Train Station. The purpose of this study was to determine the effect of service quality, Promotion, and Ease of Use of the KAI Access application partially and simultaneously on customer satisfaction of PT Kereta Api Indonesia (Persero) at Simpang Haru Train Station. The data collection methods used were questionnaires, interviews and observations.The implementation of the Access by KAI application at Simpang Haru Train Station has been running well, supporting customer convenience in ordering tickets and accessing schedule information.